Muscle plasticity after weight and combined (weight + jump) training - Toumi, H.; Best, T. M.; Martin, A.; Poumarat, G. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: The purpose of this study was to compare the effects of jump training as a complement to weight training on jump performance and muscle strategy during the squat and countermovement jump. METHOD: Twenty-two male handball players, between the ages of 17 and 24, and in good health, were randomly divided into three groups. Two were trained groups, weight training (WTG) and jump training combined with weight training (CTG), and one was a control group (CG). Maximal isometric force and maximal concentric power were assessed by a supine leg press, squat jump (SJ), counter movement jump (CMJ), and surface EMG was used to determine changes in muscle adaptation before and after the training period. RESULTS: After 6-wk training programs, the two training groups increased maximal isometric force, maximal concentric power, and squat jump performance. However, only combined training presented a significant increase in height jump performance during the countermovement jump (P < 0.05). EMG analysis (as interpreted through the root mean square values) showed that the SJ was performed similarly before and after the training period for the two training groups. However, during the CMJ, only the CTG group adopted a new technique manifested by a short transition phase together with an increase in knee joint stiffness and knee extensor muscle activation and rectus femoris ratio. CONCLUSION: It was suggested that the central activities in knee joint during the transition phase, in conjunction with intrinsic muscle contractile properties, play a major role in the regulation of performance during a CMJ. Furthermore, our study suggests that a change in maximal strength and/or explosive strength does not necessarily cause changes in combined movement such as the stretch shortening cycle.